El profesor universitario de Comunicación: acceso, consumo y cultura mediática. Un estudio comparativo entre España y México. - Martínez Sanz, Raquel; Islas Carmona, Octavio; Campos Domínguez, Eva; Redondo García, Marta (Revista Latina de Comunicación Social, 2016)
Justification. The professors of Communication transfer many of the previously consumed items to the classroom, as a basis for case-studies. Methodology. This paper analyzes, by means of survey techniques, the media consumption of Spanish (Valladolid University) and Mexican professors (La Salle University, Mexico City), assessing their informational habits, their priority, and their perception of quality assigned to the different media, as well as their extent of interactivity with them. Results and conclusions. Findings reveal that the professors' access to press, radio and television, besides being daily, demonstrates the prevalent use of traditional supports and formats; in addition, the latest types of information devices - smartphone, tablet and laptop - show an intermediate penetration among these professionals; finally, we find the fact that the professors interact with journalistic companies primarily through comments on the most relevant news, made in social networks.